Begrebet ’irregularitet’ i den middelalderlige kirke - Ingesman, Per (Religionsvidenskabeligt Tidsskrift, 1997)
A series of registres in the archives of the Papal Penitentiary in Rome, only recently made accessible to historical research, contain papal absolutions and dispensations from the Later Middle Ages in large numbers. Many of them are dealing with irregularity, a canon law concept designating various hindrances to ordination. After a short introduction to the Penitentiary and its archives, the first part of the articles examines the different forms of irregularity as described in canon law, trying to compare legal prescriptions with administrative practice. The second part of the article examines in detail the most common form of irregularity in the registers of the Penitentiary, namely that illegitimate persons because of their so-called "birth defect" could not enter the clerical profession without a papal dispensation. Having followed the development of this idea from the early 9th to the late 13th century, the article in its conclusion discusses how to interpret the concept of irregularity compared to more well-known forms of religious uncleanness. It is argued that the canon law concept is a complex one, through which the medieval Church tried not only to secure the cleanness of the clergy because of its liturgical functions, but also to uphold Church authority and clerical reputation and to prevent people totally unfit for an ecclesiastical career from entering the profession.